2020
DOI: 10.1111/josh.12985
|View full text |Cite
|
Sign up to set email alerts
|

Teacher Experience, Personal Health, and Dieting Status Is Associated With Classroom Health‐Related Practices and Modeling*

Abstract: BACKGROUND Evidence suggests that schools play an important role in student health; however, little is known about variability in teachers' use of food‐related classroom practices. In this study, we examined associations between teacher demographic and individual factors and their food‐related practices and modeling in the classroom. METHODS We had 239 teachers in the United States complete an online survey about their demographics (years of teaching experience, socioeconomic status of the school), personal he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 44 publications
0
9
0
Order By: Relevance
“…Teachers’ health-related behaviours are important because they lead to positive health outcomes for teachers themselves and because teachers model health behaviours to their students ( Bevelander et al ., 2013 ; Findholt et al, 2016 ; Hamilton et al , 2021 ). Teachers’ own health behaviours may influence their confidence in delivering health education programs in schools ( Kennedy et al ., 2019 ; Herlitz et al ., 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Teachers’ health-related behaviours are important because they lead to positive health outcomes for teachers themselves and because teachers model health behaviours to their students ( Bevelander et al ., 2013 ; Findholt et al, 2016 ; Hamilton et al , 2021 ). Teachers’ own health behaviours may influence their confidence in delivering health education programs in schools ( Kennedy et al ., 2019 ; Herlitz et al ., 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Teachers’ health and wellbeing, including food and nutrition (FN) practices are influenced by professional workload and school environment [ 1 ], while they in turn have an influence on the students within their care as role models [ 2 ], health promoters [ 3 , 4 ], gate keepers [ 5 ], and FN educators [ 6 ]. While high rates of teacher work-related stress and burnout have been identified as contributors to teacher turnover, highlighting the impact of teacher wellbeing on performance of work-related tasks, the influence of FN practices on teacher wellbeing has not been explored [ 1 , 7 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…Youth whose parents eat [ 9 , 10 , 12 ] or encourage [ 12 ] a healthy diet are more likely to consume healthy foods. Students have also reported that social support from their friends, family, and teachers [ 13 ], as well as role-modeling behaviors of adults, enhances their likelihood of eating healthy foods [ 11 ]. It is not clear, however, if these adult influences apply in the school lunch context, and particularly, if teachers can positively influence youth participation in the NSLP.…”
Section: Introductionmentioning
confidence: 99%